La información espacial e iconográfica en la investigación antropológica - Hernández C., Enrique (2023)
The professional exercise of anthropological investigation has made to experiment different forms of relationship and capture of realities that have been taken like study objects. Each case, makes important exercises of exploration and design of strategies, procedures and technics that make possible to know, to organize, to analyze and to interpret those realities. The opportunity to make the investigation, “Identidad cultural en Llano Grande de Pacayas”, let me think about the importance to promote the discussion related to the resources of investigation that at the present are used by anthropologies, to evaluate its impact, to share experiences. Spatial and iconographic information is a kind of knowledge in constant relation with anthropology. For this reason the proposed study offers a first approach to its delimitation and comprehension, definition, uses, characteristics, and limitation of that information.